The miraculous baby: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Miraculous Baby" tells the story of a miraculous birth, often associated with a divine or special purpose. It highlights themes of hope, faith, and the extraordinary potential of new life. The narrative typically emphasizes the significance of the baby's arrival in changing the lives of those around them and the belief that great things can emerge from humble beginnings.